La La costruzione del sociale nell’epoca della postrealtà - Grassi, Edmondo (SocietàMutamentoPolitica, 2023)
In a contemporaneity in progress, the emergence of disruptive phenomena, unexpected and not underlying the rules of control and immediate quantification, induces the subject to a continuous representation and participation in the public debate, driven by the need to regain possession, even if only apparently, of the space of a mixture in which reality and fiction are contaminated in a relationship of continuous exchange until it is impossible to resolve their factuality and their construction. The intent is to theoretically outline the contours and the correlation phenomena between the understanding and manipulation of reality and the elements of communication, identity formation and social implications through the spread of social networks, deep fakes and artificial intelligence in the post-reality period.